Pengembangan Media Komik Digital Echt Spass dengan Tema Schule untuk Pembelajaran Bahasa Jerman Kelas X - Puji Indah Lestari; Lilis Afifah (Universitas Negeri Malang, 2021)
Abstract: This research is development research that produces a product in the form of a digital comic application “Echt Spaß” as a German language learning media for students. The purpose of developing comics media is to solve the problem of lack of visualization of German language learning materials. The theme used is Schulleben (school life) which is the material for class X in even semester. The digital comic application “Echt Spaß” contains learning material in the form of comics, including Grammatik und Wortschatz (grammar and vocabulary), and practice questions are also presented. The development of digital comics is expected to be able to train students’ reading (Lesen), writing (Schreiben), and speaking (Sprechen) skills. The method used in this research is research and development and follows the Richey, Klein, and Nelson type one model. The developer uses a qualitative descriptive data analysis technique with the target user being class X language students at SMAN 1 Gondanglegi Malang. Based on the results of the validation by experts, it can be concluded that the developed media is feasible to use in the learning process. The testing stage also shows a positive result. That is, most students agreed that the “Echt Spaß” digital comic application could help in learning German as a foreign language. Keywords: digital comics; learning media; German language Abstrak: Penelitian ini merupakan penelitian pengembangan yang menghasilkan produk berupa aplikasi komik digital “Echt Spaß” sebagai media pembelajaran bahasa Jerman untuk siswa kelas X. Tujuan dikembangkannya media komik ialah untuk memberikan solusi atas permasalahan kurangnya visualisasi terhadap materi pembelajaran bahasa Jerman. Tema yang digunakan adalah Schulleben (kehidupan sekolah) yang merupakan materi kelas X semester genap. Aplikasi komik digital “Echt Spaß” berisi materi pembelajaran berupa komik yang didalamnya memuat Grammatik und Wortschatz (tata bahasa dan kosakata), selain itu disajikan pula soal-soal latihan. Dikembangkannya komik digital ini diharapkan dapat melatih keterampilan membaca (lesen), menulis (schreiben) dan berbicara (sprechen) pada siswa. Metode yang digunakan pada penelitian ini adalah penelitian dan pengembangan (research and development) dan mengikuti model Richey, Klein dan Nelson tipe satu. Penulis menggunakan teknik analisis data deskriptif kualitatif dengan sasaran pengguna yakni siswa kelas X Bahasa SMAN 1 Gondanglegi Malang. Setelah melalui tahap validasi, revisi dan uji coba kelayakan, sebagian besar siswa setuju bahwa aplikasi komik digital “Echt Spaß” dapat membantu mereka dalam proses pembelajaran bahasa Jerman, sehingga produk aplikasi komik digital “Echt Spaß” ini dinilai layak untuk digunakan. Kata kunci: komik digital; media pembelajaran; bahasa Jerman